Aberrant epigenome in iPSC‐derived dopaminergic neurons from Parkinson's disease patients. Issue 12 (29th October 2015) - Fernández‐Santiago, Rubén; Carballo‐Carbajal, Iria; Castellano, Giancarlo; Torrent, Roger; Richaud, Yvonne; Sánchez‐Danés, Adriana; Vilarrasa‐Blasi, Roser; Sánchez‐Pla, Alex; Mosquera, José Luis; Soriano, Jordi; López‐Barneo, José; Canals, Josep M; et al.
Abstract: The epigenomic landscape of Parkinson's disease (PD) remains unknown. We performed a genomewide DNA methylation and a transcriptome studies in induced pluripotent stem cell (iPSC)‐derived dopaminergic neurons (DAn) generated by cell reprogramming of somatic skin cells from patients with monogenic LRRK2‐associated PD (L2PD) or sporadic PD (sPD), and healthy subjects. We observed extensive DNA methylation changes in PD DAn, and of RNA expression, which were common in L2PD and sPD. No significant methylation differences were present in parental skin cells, undifferentiated iPSCs nor iPSC‐derived neural cultures not‐enriched‐in‐DAn. These findings suggest the presence of molecular defects in PD somatic cells which manifest only upon differentiation into the DAn cells targeted in PD. The methylation profile from PD DAn, but not from controls, resembled that of neural cultures not‐enriched‐in‐DAn indicating a failure to fully acquire the epigenetic identity own to healthy DAn in PD. The PD‐associated hypermethylation was prominent in gene regulatory regions such as enhancers and was related to the RNA and/or protein downregulation of a network of transcription factors relevant to PD (FOXA1, NR3C1, HNF4A, and FOSL2). Using a patient‐specific iPSC‐based DAn model, our study provides the first evidence that epigenetic deregulation is associated with monogenic and sporadic PD. Synopsis: This is the first proof‐of‐principle that induced pluripotent stem cell (iPSC)‐derived dopaminergic neurons (DAn) from sporadic and monogenetic Parkinson's disease (PD) patients show the same epigenomic changes as compared to healthy controls. For a video version of this synopsis, see:http://embopress.org/video_EMM-2015-05439 . Epigenomic changes are common in patients with sporadic PD and patients with a monogenic form of PD associated with mutations in the gene LRRK2. PD‐associated methylation changes are latent in parental somatic cells or undifferentiated iPSCs and become uncovered upon differentiation into DAn (cells targeted in PD) but not into other neural types. PD‐associated methylation changes correlate with gene expression, target functionally‐ active sequences (enhancers), and are related to the aberrant down‐regulation of a network of transcription factors relevant to PD. Abstract : This is the first proof‐of‐principle that induced pluripotent stem cell (iPSC)‐derived dopaminergic neurons (DAn) from sporadic and monogenetic Parkinson's disease (PD) patients show the same epigenomic changes as compared to healthy controls.